Towards Better Governance on Biosafety and Biosecurity: China’s Advances and Perspectives in Medical Biotechnology Legislation - Xue, Yang; Shang, Lijun (Frontiers in Bioengineering and Biotechnology, 2022)
In this paper, we systematically investigated and assessed China’s evolving medical biotechnology legislative and regulatory regime. 89 laws, rules, measures, guidelines, and views from 1985 to 2022 were systematically analogized and 28 were found to be involved in medical biotechnology legislation, including the recently passed Biosecurity Law. We classified the legislations and performed a comparative analysis for their legal binding based on the legal subject and extent of application, then further analyzes some of the legislative challenges in governing medical biotechnology risks in the context of China’s upgrading its regulatory and legal regime in the last 3 years. We concluded that policymakers in China have now incorporated medical biotechnology-related biosafety and biosecurity into the national strategic goals of a “People-Centered” approach to establish and foster an ecological civilization, particularly in the aftermath of the “He Jiankui affair.” Instead of relying on a patchwork of existing regulations and measures relating to the emerging field of medical biotechnology, China is attempting to integrate a patchwork of existing regulations and measures into a comprehensive legal framework, such as the constitution, National Security Law, Biosecurity Law, administrative regulations, departmental and local rules, and has begun to use the Civil Code and Criminal Law to explicitly identify actions relating to medical biotechnology. In general, China follows the “precautionary principle” as it thinks that uncertainty in science and technology should not be used to justify delaying the adoption of measures to prevent injuries or dangers, stating that whoever advances biotechnology must face the burden of proof of no harm. There would be a need to impose oversight for prevention and precaution if any biotechnology breakthrough that carries risks on which no scientific consensus has been reached. We argued that the “top-down” formulation of general objectives by the active political leadership and “bottom-up” innovation in the implementation are the keys to achieving these goals. Given the rapid advancements in medical biotechnology, countries all over the world must examine the governance landscape around biosafety and biosecurity and quickly consider options for their own comprehensive, credible, and long-lasting regulatory frameworks and experiences learned from China’s governance will help chart a scalable future roadmap.